Study on Method for Measuring Coating Emissivity by Applying Active Irradiation Based on Infrared Thermal Imager - Yiwen Li; Puyousen Zhang; Ge Chen; Yao Li; Weizhuo Hua; Yuqin Li; Zhaoqiang Jiao (Sensors, 2022)
To achieve rapid and precise non-contact measurements of coating emissivity at room temperature, a measurement method based on infrared thermal imager was proposed. By applying two irradiations with different energies to the target and reference surfaces, the influences of atmospheric transmittance, radiation of the target itself, environmental radiation, and atmospheric path radiation were eliminated, thereby enabling accurate emissivity measurement. Experiments were designed for validation with a mid-wave infrared thermal imager and a surface blackbody as the radiation source. Several combinations of irradiation energy were set to investigate the effects of average energy and energy difference between the two irradiations on the measured results. The normal emissivity of the coated sample plate in the mid-wave band was measured to generate the image of coating surface emissivity. Then, the emissivity measurement results of the proposed method were compared with those of the energy method and the point emissivity measuring instrument under the same conditions, and the comparison indicated that the proposed method can effectively measure the emissivity of coating. Some factors causing measurement errors were analyzed. Finally, an experiment was designed to compare the measurement speed between the proposed method and the currently used methods, and the experimental results were analyzed.